Compliance of healthcare workers with the infection prevention and control guidance in tertiary care hospitals: quantitative findings from an explanatory sequential mixed-methods study in Bangladesh - Syed Shariful Islam; Syed Moniruzzaman; M Atiqul Haque; Sarmin Sultana; Marium Salwa; Mohammad Tanvir Islam; Md Maruf Haque Khan (BMJ Open)
Objectives To assess healthcare workers’ (HCWs) compliance with the infection prevention and control (IPC) practices and identify the factors influencing this compliance using the Health Belief Model as the theoretical framework.Design Quantitative data from an explanatory sequential mixed-methods study were employed in this research.Participants and settings From 17 May to 30 August 2020, 604 physicians and nurses working at six randomly selected tertiary care facilities in Dhaka City in Bangladesh took part in this study.Primary and secondary outcome measures Compliance with the WHO’s guidance on IPC measures, as well as the associated factors, was the primary outcome.Results A mean compliance score of 0.49 (±0.25) was observed on a 0–1 scale. HCWs were most compliant with the medical mask wearing guidelines (81%) and were least compliant with the high-touch surface decontamination regulations (23%). Compliance with the IPC guidance was significantly associated with increasing age, female sex, working as a nurse, having non-communicable diseases and history of exposure to patients with COVID-19. Perceived benefits (B=0.039, 95% CI 0.001 to 0.076), self-efficacy (B=0.101, 95% CI 0.060 to 0.142) and cues to action (B=0.045, 95% CI 0.002 to 0.088) were positively associated with compliance. Compliance with IPC guidance was 0.061 times greater among participants who reported low perceived barriers compared with those with high perceived barriers.Conclusion Overall, compliance with IPC guidance among HCWs was unsatisfactory. As self-efficacy exerted the greatest contribution to compliance, it should be emphasised in any endeavour to improve HCWs’ IPC adherence. Such interventions should also focus on perceived barriers, including unreliability of the information sources, unsafe working places and unavailability of protective equipment and cues to action, including trust in the administration and availability of adequate IPC guidance.